Use of fish embryo toxicity tests for the prediction of acute fish toxicity to chemicals. (27th June 2013) - Belanger, Scott E.; Rawlings, Jane M.; Carr, Gregory J.
Abstract: The fish embryo test (FET) is a potential animal alternative for the acute fish toxicity (AFT) test. A comprehensive validation program assessed 20 different chemicals to understand intra‐ and interlaboratory variability for the FET. The FET had sufficient reproducibility across a range of potencies and modes of action. In the present study, the suitability of the FET as an alternative model is reviewed by relating FET and AFT. In total, 985 FET studies and 1531 AFT studies were summarized. The authors performed FET–AFT regressions to understand potential relationships based on physical–chemical properties, species choices, duration of exposure, chemical classes, chemical functional uses, and modes of action. The FET–AFT relationships are very robust (slopes near 1.0, intercepts near 0) across 9 orders of magnitude in potency. A recommendation for the predictive regression relationship is based on 96‐h FET and AFT data: log FET median lethal concentration (LC50) = (0.989 × log fish LC50) − 0.195; n  = 72 chemicals, r  = 0.95, p  < 0.001, LC50 in mg/L. A similar, not statistically different regression was developed for the entire data set ( n  = 144 chemicals, unreliable studies deleted). The FET–AFT regressions were robust for major chemical classes with suitably large data sets. Furthermore, regressions were similar to those for large groups of functional chemical categories such as pesticides, surfactants, and industrial organics. Pharmaceutical regressions ( n  = 8 studies only) were directionally correct. The FET–AFT relationships were not quantitatively different from acute fish–acute fish toxicity relationships with the following species: fathead minnow, rainbow trout, bluegill sunfish, Japanese medaka, and zebrafish. The FET is scientifically supportable as a rational animal alternative model for ecotoxicological testing of acute toxicity of chemicals to fish. Environ Toxicol Chem 2013;32:1768–1783. © 2013 SETAC